Answer:
Step-by-step explanation
Step 1: multiply the coefficient a and the constant c. Given that the general expression of a parabolic equation is ax^2+bx+c
3*5=15
Step 2: examine the coefficient b and try to find 2 numbers which you can multiply to get 15, add or subtract and get - 8
In this Case: - 3*-5=15 and - 3+(-5)= - 8
Step3:
You separate the equation in terms of the two factors you have found
3x^2-3x-5x+5=0
Step 4:Factorise
3x(x-1)-5(x-1)=0
(3x-5)(x-1)=0
Answer:
Step-by-step explanation:
A picture is needed for this
Answer:
(a) x² − 13x + 4
(b) x² − 26x + 153
Step-by-step explanation:
f(x) = x² + 3x − 2
a + ß = -3
aß = -2
(a) (x − a²) (x − ß²)
x² − (a² + ß²) x + a²ß²
x² − ((a + ß)² − 2aß) x + a²ß²
x² − ((-3)² − 2(-2)) x + (-2)²
x² − (9 + 4) x + 4
x² − 13x + 4
(b) (x − (a − ß)²) (x − (a + ß)²)
x² − ((a − ß)² + (a + ß)²) x + (a − ß)²(a + ß)²
x² − (a² − 2aß + ß² + a² + 2aß + ß²) x + (a² − 2aß + ß²)(a + ß)²
x² − (2a² + 2ß²) x + (a² − 2aß + ß²)(a + ß)²
x² − 2(a² + ß²) x + (a² − 2aß + ß²)(a + ß)²
x² − 2((a + ß)² − 2aß) x + ((a + ß)² − 4aß)(a + ß)²
x² − 2((-3)² − 2(-2)) x + ((-3)² − 4(-2))(-3)²
x² − 2(9 + 4) x + (9 + 8)(9)
x² − 26x + 153
Answer:
A=4.80:1.20 B=1.20:4.80
Step-by-step explanation: